Protocol to identify host-viral protein interactions between coagulation-related proteins and their genetic variants with SARS-CoV-2 proteins - David D. Holcomb; Katarzyna I. Jankowska; Nancy Hernandez; Kyle Laurie; Jacob Kames; Nobuko Hamasaki-Katagiri; Anton A. Komar; Michael DiCuccio; Chava Kimchi-Sarfaty (STAR Protocols, 2022)
Summary: Here, we describe a bioinformatics pipeline that evaluates the interactions between coagulation-related proteins and genetic variants with SARS-CoV-2 proteins. This pipeline searches for host proteins that may bind to viral protein and identifies and scores the protein genetic variants to predict the disease pathogenesis in specific subpopulations. Additionally, it is able to find structurally similar motifs and identify potential binding sites within the host-viral protein complexes to unveil viral impact on regulated biological processes and/or host-protein impact on viral invasion or reproduction.For complete details on the use and execution of this protocol, please refer to Holcomb et al. (2021). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.